2014
DOI: 10.5539/ijef.v6n10p191
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Budget Deficit Policies in Economic Growth from A Keynesian Perspective

Abstract: Functional fiscal policy implementation has always been a matter of debate particularly in recessed economies. This study aims to analyze the European Debt Crisis stemming from the 2008 Global Crisis within Keynesian budget deficit policies. We examined the best 5 and worst 5 countries in the Eurozone according to their debt ratios and discussed the growth rates, debt ratios and budget deficit variables of these countries. Panel ARDL model was used for the 2000Q1-2011Q4 period. The analysis results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Adam and Bevan (2005) show results that the budget deficit of 1.5 per cent of GDP will have a positive impact on economic growth. Cinar at al. (2014) analyzed a group of five countries with a debt ratio for the lowest GDP and five other countries where the debt ratio was large in the euro area for the period 2000 -2011, with the help of the ARDL panel model they found that deficit policy had a positive effect on economic growth in the short term.…”
Section: Resultsmentioning
confidence: 99%
“…Adam and Bevan (2005) show results that the budget deficit of 1.5 per cent of GDP will have a positive impact on economic growth. Cinar at al. (2014) analyzed a group of five countries with a debt ratio for the lowest GDP and five other countries where the debt ratio was large in the euro area for the period 2000 -2011, with the help of the ARDL panel model they found that deficit policy had a positive effect on economic growth in the short term.…”
Section: Resultsmentioning
confidence: 99%
“…According to the author, a productive expenditure rather had a positive and significant relation with economic growth. Cinar, Eroglu and Demirel (2014) also employed the panel ARDL model to analyze the European Debt Crisis stemming from the 2008 Global Crisis within Keynesian budget deficit policies using data from 2000Q1-2011Q4. The study revealed that conjunctural deficit policy (functional fiscal policy) had a positive effect on economic growth in the short run.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They support the 'Golden Rule' of public finance and argue that the fiscal deficit amount should be used for capital formation purpose and not for the current consumption of the Government. Cinar et al (2014) examined the best five (5) and worst five (5) countries in the Eurozone according to their debt ratios and discussed the growth rates, debt ratios and budget deficit variables of these countries with special focus on the period 2008 and the recent Great Recession of [2007][2008][2009]. The authors used a Panel ARDL model for the 2000Q1-2011Q4 period.…”
Section: Literature Reviewmentioning
confidence: 99%